STRATEGI KOMUNIKASI POLITIK PARTAI KEBANGKITAN BANGSA (PKB) KABUPATEN JEMBER MENJELANG PEMILUKADA JAWA TIMUR 2018 - Muhamad Farhan (Al'Adalah, 2019)
Indonesia is one of the countries that embrace the system of democratic government. In a democratic state the people have sovereignty, this is done to ascertain who deserves to be a leader. The Party is an organization that represents the people and means of public participation to participate. Electoral parties compete for leadership seats (power) by strategizing to win them. Elections (elections) is the process of electing people to fill positions within the government. The positions are diverse, ranging from the President, People's Representatives at various levels of government, to the Village Head. Elections as a means to participate in the people persuasively (not forced) to the government, so as to realize the principles of democracy in the implementation. The election is a means for political parties to place their cadres in strategic positions in government either executive (President, Governor, Regent, Mayor, etc.) or legislative (Regency, Provincial and Central DPRD) to seize power, not to mention Partai Kebangkitan Bangsa (PKB) Jember district in the face of elections East Java area. various political communication strategies are used to hook as many constituents for the achievement of goals. The formulation of the problem in this Thesis is: How is the communication strategy of the Partai Kebangkitan Bangsa (PKB) of Jember Regency ahead of the election of General Head of Region (Pemilukada) of East Java 2018. The purpose of this research is to describe the communication strategy used by the Partai Kebangkitan Bangsa (PKB) of the Jember Regency ahead of the elections of Regional Head (Pemilukada) of East Java 2018 to get the constituents from Jember society which is quite diverse. This research uses a descriptive qualitative approach. With the data collection method of observation and documentation. The research concludes that the Partai Kebangkitan Bangsa (PKB) of Jember Regency divides its political communication strategy according to age ie political communication among young people and political communication among parents. Political communication among youth is done through the program of open together, coffee with PKB Jember, and halal bi halal. Whereas political communication among parents is implemented through the program of maintaining and maintaining the intensity of communication with leaders of both structural figures such as senior officials of an institution or mass organization or culture such as public figure.